The Aplication of Learning Models of Project Based Learning to Improve Students’ Learning Outcomes in Post-Legal Materials - Faradhillah, Faradhillah; Zahara, Syarifah Rita (International Journal for Educational and Vocational Studies, 2021)
This  study is motivated by the low learning outcomes of students of class VIII 3 SMP Negeri 2 Meurah Mulia which is known from the observations. The research objective was to determine the improvement of learning outcomes in the Pascal Law material for class VIII 3 students of SMP Negeri 2 Meurah Mulia by using project based learning (pjbl) of learning model. This research is a type of classroom action research with a model developed by Kemmis and Mc. Taggart. The study subjects were students of class VIII 3, with a total of 16 students. The techniques used in data collection are tests, observation, interviews and documentation. This study consisted of 2 (two) cycles where there were two meetings in each cycle. The data analysis technique used a qualitative descriptive analysis. The study success criteria set for student learning outcomes is 75 for a scale of 1-100 grading. The results showed that the application of the project based learning (pjbl) of learning model could improve the learning outcomes of class VIII 3 students of SMP Negeri 2 Meurah Mulia. The average learning outcomes in cycle I was 73.16 and in cycle II increased to 82.51. In conclusion, the application of the project based learning model can improve student learning outcomes in science learning class VIII 3 SMP Negeri 2 Meurah Mulia.